Biochar from Slow Catalytic Pyrolysis of Spirulina platensis Residue: Effects of Temperature and Silica-Alumina Catalyst on Yield and Characteristics - Siti Jamilatun; Ilham Mufandi; Arief Budiman; Suhendra Suhendra (Jurnal Rekayasa Proses, 2020)
The use of biochar varies on its ability as an adsorbent which adsorbs liquid or gas molecules. Biochar from Spirulina platensis residue (SPR) as an energy source, as its richness in nutrients, can be used as fertilizer and maintain water resources in plantations. Biochar can be used as an intermediary for the synthesis of nanotubes, activated carbon, carbon black, and carbon fiber. One of the essential things to be considered in the application of activated carbon from SPR is char’s characteristics. This study aimed to obtain data on the biochar and components from the pyrolysis of Spirulina platensis residue. The study was conducted in a fixed-bed reactor with electric heaters with a variety of temperatures (300-700 ⁰C) and the amount of silica-alumina catalyst (0-20%). The biochar weight was obtained by weighing the char formed at the end of the pyrolysis. The char characteristics were obtained by the surface area, total pore volume, and pore size analysis. Based on the study results, the relationship between temperature and the amount of catalyst on the characteristics of biochar was studied. The higher the pyrolysis temperature, the less biochar. Also, the use of catalysts can reduce the amount of biochar. The higher the temperature, the higher the surface area and the total pore volume while the pore radius was reduced. The optimum condition for maximum biochar yield in non-catalytic pyrolysis at a temperature of 300 ⁰C was 49.86 wt.%. The surface area, the total pore volume, and the pore radius at 700 ⁰C catalytic pyrolysis with 5% silica-alumina was obtained as 36.91 m2/g, 0.052 cm3/g, and 2.68 nm, respectively.Keywords: biochar; pore radius; silica-alumina; surface area; total pore volumeA B S T R A KPenggunaan biochar bervariasi pada kemampuannya sebagai adsorben dalam menjerap molekul cairan atau gas. Biochar dari residu Spirulina platensis merupakan sumber energi, karena kaya akan unsur hara, dapat digunakan sebagai pupuk dan pemeliharaan sumber daya air di perkebunan. Biochar dapat juga digunakan sebagai perantara untuk sintesis nanotube, karbon aktif, carbon black, dan serat karbon. Salah satu hal penting yang harus diperhatikan dalam aplikasi karbon aktif dari SPR adalah karakteristik arang. Penelitian ini bertujuan untuk mendapatkan data biochar dan komponen dari pirolisis residu Spirulina platensis. Penelitian dilakukan di reaktor fixed-bed dengan pemanas listrik dengan variasi suhu (300-700 ⁰C) dan jumlah katalis silika-alumina (0-20%). Berat biochar diperoleh dengan cara menimbang arang yang terbentuk pada akhir pirolisis. Sedangkan karakteristik arang diperoleh dari analisis luas permukaan, volume pori total, dan ukuran pori. Berdasarkan hasil studi hubungan antara suhu dan jumlah katalis terhadap karakteristik biochar yang telah diteliti, semakin tinggi suhu pirolisis maka biochar semakin sedikit. Selain itu, penggunaan katalis dapat mengurangi jumlah biochar. Sebaliknya, semakin tinggi suhu semakin besar luas permukaan, dan volume pori total serta radius pori-pori semakin berkurang. Kondisi optimum untuk biochar maksimum pada pirolisis non katalitik pada suhu  300 ⁰C adalah 49,86 wt.%. Luas permukaan, total volume pori, dan radius pori pada suhu 700 ⁰C untuk pirolisis katalitik silika-alumina 5% diperoleh masing-masing sebesar 36,91 m2/g, 0,052 cm3/g, dan 2,68 nm.Kata kunci: biochar; luas permukaan; radius pori; silika-alumina; total volume pori